PANDANGAN ISLAM TENTANG KESEJAHTERAAN SOSIAL BAGI KELOMPOK PENYANDANG DISABILITAS - Miftahur Ridho (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2017)
The aim of this paper is to understand dynamics of social welfare from an Islamic standpoint. Both texts and historical record of Islam show that Islam put people with disabilities in an honorable position, and set a range of regulation to elevate their dignity. Based on Islamic perspective, this group must be treated equally as their normal counterpart. Hence, the distribution of social welfare should be based on the worth and dignity of people with disabilities. Provision of social welfare to people with disabilities, therefore, must be assessed proportionally. Assuming that every person with disabilities has the same needs tends to transform social welfare provision into oppressive forms. Keywords: Social welfare, Islam, disabilities.